Performance Analysis and Added Value of Industry Processing Beef into Processed Meat Jengken and Shredded in the Kota Kefamenanu District - VICTORIA SARI LAU; Stefanus Sio; Theresia Ika Purwatiningsih; Hilarius Y. Sikone (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2021)
This research aims to determine the performance of the beef processing industry in Kefamenanu City District and to analyze the amount of added value generated from beef processing in Kefamenanu City District. This research was conducted in the MSMEs VIVI meat processing industry, Kefamenanu City District, North Central Timor Regency. This study used the Surfei method with quantitative descriptive analysis. The variables observed were the performance of the meat processing industry and the added value of beef processing. The application of the balanced scorecard concept in analyzing the performance of VIVI MSMEs shows that from a financial perspective it has a good performance with an infinite CR value; average NPM 8,216%; an average ROA of 15,39% and an average ROI of 2,24 times of the investment value. From the customer perspective, it has a good performance with 51,49% of general customers who are satisfied and 49,79% of partner customers who are satisfied. For the perspective of internal business processes and the perspective of learning and growth have a good performance, respectively, with a value of 60,76% and 54,86%, respectively. It is concluded that the value added of beef products per kilogram of output is Rp. 48.060.00 for shredded products and beef jerky products of Rp. 37.551.00.